Personal factor and consumer purchase intention: the risen of coffee culture in Klang Valley, Malaysia / Nur Yasarah Yahya, Nurin Adini Mazlan and Wan Nor Bayah Wan Kamarudin - Yahya, Nur Yasarah; Mazlan, Nurin Adini; Wan Kamarudin, Wan Nor Bayah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
The consumption of coffee has become increasingly popular in Malaysia, especially among adolescents and the millennium generation. Therefore, the Malaysian coffee culture has grown and flourished in tandem with the needs and demands of consumers. Hence, diverse personal aspects of consumers in influencing their buying intentions are relatively important and considered a major concern in marketing and behavioral studies. Therefore, this study aims to assess the personal factors that currently affect consumers' purchase intention among consumers in Klang Valley, Malaysia. Quantitatively, this study has conducted an online survey among 398 respondents by using non-probability sampling in the Klang Valley. The result reveals that only four (4) personal factors are perceived namely; (1) age and life cycle, (2) occupation, (3) income, and (4) personality have a significant relationship to consumer purchase intentions. In conjunction with it, personality is the most important factor among personal factors affecting consumer purchase intentions among coffee consumers in the Klang Valley, Malaysia. Henceforth, personal factors are among the significant factors that contribute to consumer purchase intentions. It is recommended that business owners of coffee shops should invest in relevant sales strategies to encounter their consumer preferences and personal factors. This will provide a competitive advantage to business owners as consumer trends and behaviors are constantly transformed according to different generations and settings of environments.